Digitalization of the Macedonian public administration: a pathway to prevent maladministration and illegal activities - Bitrakov, Konstantin (Department of Business Law, Faculty of Economic and Social Sciences of the Budapest University of Technology and Economics, Budapest, Hungary Department of Law, Faculty of Law & Management, University of Mauritius, Mauritius Department of Private International Law, Faculty of Law, University of Szeged, Szeged, Hungary Faculty of Law and Business Studies Dr Lazar Vrkatić, Novi Sad, Serbia Faculty of Law, Ankara Yıldırım Beyazıt University, Ankara, Turkey Faculty of Law, Yozgat Bozok University, Yozgat, Turkey Iustinianus Primus Faculty of Law, Ss. Cyril and Methodius University, Skopje, Macedonia, 2023)
The global shift towards the digitalization of public administration presents a potent force in improving service delivery, efficiency, and curbing maladministration. This paper explores this transition in the Republic of North Macedonia, emphasizing the potential of digital platforms like e-governance portals and eIDs in reducing bureaucracy and fostering accessibility to public services. Despite the positive strides, a concrete evaluation of its impact remains elusive. The paper is segmented into several sections. Initially, it establishes a theoretical foundation, correlating digitalization with reduced maladministration, supplemented by comparative experiences. Following this, the focus shifts to the specific national context, discussing citizens' perceptions and other key indicators concerning maladministration and illicit activities. Subsequent sections delve into an analysis of Macedonia's recent legislation and ongoing projects, such as the National Portal of e-Services and the Catalogue of Services, assessing their efficacy and implementation hurdles like law inconsistencies and limited technological infrastructure. In conclusion, the paper underscores the necessity for a comprehensive approach to digitalization, encompassing legislative amendments and organizational reforms, alongside technological advancements. While Macedonia has initiated this process, sustained efforts are vital to surmount existing obstacles and maximize the benefits of digital technology in mitigating maladministration.
Keywords: digitalization, Macedonian administration, maladministration, digital transformation, electronic services